ID: 9: AN IL7 MONOCLONAL ANTIBODY RESCUES HYPOXIA-MEDIATED PULMONARY HYPERTENSION IN MICE. Issue 4 (22nd March 2016) - Gao, H; Dong, Y; Machado, RF; Chen, J
Abstract : Rationale: Previously we showed that human plasma IL7, protein levels of IL7 receptor (IL7R) in total lung homogenate and pulmonary artery endothelial cells (PAECs)/PASMCs were significantly elevated in PAH patients. IL7 promotes PASMC proliferation. IL7R-deficient (IL7R −/− ) mice are protected from hypoxia-mediated pulmonary hypertension (HPH). We sought to study whether blocking IL7 via anti-IL7 antibodies can reverse experimental PH in mice. Methods: Male C57BL/6 mice (7 week old) were exposed to normoxia or hypoxia (10% O2 ) for 4 weeks (n=6 per group). At Day 12 after hypoxia exposure, a monoclonal antibody against IL7 (AB-407-na, R&D Systems) or control IgG was started to treat the mice (100 µg/mouse, every other day, IP, for two weeks). Right ventricular systolic pressure (RVSP) was determined with a Millar pressure transducer catheter. The right ventricle: left ventricle +septum (RV/LV+S) ratio was calculated. Pulmonary artery remodeling was assessed using Aperio image software. Result: After four weeks of hypoxic exposure, treatment of IL7 antibody significantly attenuated RVSP (28.89±0.87 vs. 34.43±2.23 mm Hg, p=0.03), developed less right ventricular hypertrophy (RVH) (RV/LV+S 0.29±0.0087 vs. 0.39±0.014, p=0.0002 ), and lower pulmonary arterial thickness when compared to control-IgG treated group. Conclusion: IL7 antibodies reverse HPH in mice. IL7 antibodies could be a novel therapeutic candidate for pulmonary hypertension.